Human Rights: An Unenforceable Concept - Manotar Tampubolon (RIRAI Publisher, 2022)
This qualitative article analyzes the idea of human rights as inalienable rights. Long before modernity changed the world, it signed many agreements to establish human rights, particularly those governing the boundaries of the authority of leaders and citizens. Although moral assumptions are involved, they have no significant impact on its enforcement. Thus, along with its limited capability, the concept of human rights is solely a decorative element of the constitution and legal framework. Under such circumstances, recognizing the significance of understanding human rights needs an all-out concerted effort, mainly from a universal perspective and a legal enforcement effort. The study seeks to determine why human rights enforcement in Indonesia is ineffective and contrary to the concept of universal human rights. The author employs qualitative research with a descriptive method to address this issue. This research is also desk (library research), as I entirely based it on library data sources on library research. In addition, it employs literature related to the enforcement of Human Rights (HAM) from a legal perspective. This study concludes that human rights enforcement in Indonesia is weak because of flaws in the law and the state's lack of political will to enforce human rights and obligations. These changes include ensuring that the enforcement of human rights is absolute and not influenced by political perspectives and motivations and thus guarantees human freedom. The author suggests that establishing a more effective institution and agency is a more critical step in the coming years.